Implementasi Matematika Veda Untuk Meningkatkan Hasil Belajar Siswa di SD Negeri 1 Tirtasari Kecamatan Banjar Kabupaten Buleleng - Kadek Erni Rosalina (Edukasi: Jurnal Pendidikan Dasar, 2020)
Learning mathematics is about abstract concepts and structures contained in mathematics and looking for relationships between concepts and mathematical structures. Learning mathematics must go through a process that survives from a simple concept to a more complex concept. Elementary mathematics learning can be done by implementing vedic mathematics. The results of the study stated in the first cycle, obtained an average student learning outcomes of 73.66 thanks to the good category while the classical completeness of 46.66% and absorption of 73.66%. Based on the results of data analysis in the second cycle, the average student learning outcomes obtained were 82 thanks to the good category, while the classical completeness was 86% and absorption was 82%. So that it can be said that the implementation of vedic mathematics has succeeded in improving the mathematics learning outcomes of elementary school students. Keywords: Vedic Mathematics and Learning Outcomes